COMPARATIVE ANALYSIS OF MOTIVATIONAL SPHERE IN PEOPLE AT DIFFERENT STAGES OF CAREER DEVELOPMENT - T M Babaev; N V Kargina (Peoples' Friendship University of Russia (RUDN University), 2015)
The problem of motives and motivation of human behavior in their activities is one of the major issues in psychology. The main way to achieve an effective professional activity of a person is to understand his or her motivation. By using the knowledge about what motivates people, encourages them to act, what motives prompt their actions, you can develop an effective system of forms and methods to manage them. It is important to understand: how the motives arise or if they are caused by various reasons at different stages of career development; how and in what ways can motives be put in action; how to motivate people.In the present work there were empirically investigated the characteristics of demonstration of the human motivational sphere, not only at the research stage, when it comes to the choice of profession and self- determination (from 15 to 24 years), but also at the later stages of a person's career: a consolidation phase of career (25 to 44 years) and a stage of the career saving (45 to 64 years)